2021
DOI: 10.1016/j.ctrv.2021.102219
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the immuno-biology of oesophageal adenocarcinoma: Towards improved therapeutic approaches

Abstract: With an incidence that is constantly rising, oesophageal adenocarcinoma (OAC) is becoming an increasing health burden worldwide. Although significant advances in treatment regimens have improved patient outcomes, survival rates for this deadly cancer remain unsatisfactory. This highlights the need to improve current therapeutic approaches and develop novel therapeutic strategies for treating OAC patients. The advent of immunotherapy has revolutionised treatment across a range of malignancies, however outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 160 publications
0
9
0
Order By: Relevance
“…ICI is now an established therapy aimed at preventing the inhibition of the anti-tumour immune response ( 44 ). The earliest trials investigating ICIs in OAC focused on treating advanced/metastatic oesophageal or gastro-oesophageal cancers with anti-PD-1, or anti-PD-L1 monoclonal antibodies ( 6 , 51 , 52 ) and have been summarised in a previous review ( 7 ). Results varied, but overall, in the advanced/palliative setting ICI appears to improve patient survival compared to chemotherapy alone.…”
Section: Treatment Evolution In Oac and Modulation Of The Tmementioning
confidence: 99%
See 1 more Smart Citation
“…ICI is now an established therapy aimed at preventing the inhibition of the anti-tumour immune response ( 44 ). The earliest trials investigating ICIs in OAC focused on treating advanced/metastatic oesophageal or gastro-oesophageal cancers with anti-PD-1, or anti-PD-L1 monoclonal antibodies ( 6 , 51 , 52 ) and have been summarised in a previous review ( 7 ). Results varied, but overall, in the advanced/palliative setting ICI appears to improve patient survival compared to chemotherapy alone.…”
Section: Treatment Evolution In Oac and Modulation Of The Tmementioning
confidence: 99%
“…Significant treatment improvement has been made in other cancer types, but ICI response in OAC is moderate. Only a minority of patients shows a complete or partial response when treated with immunotherapy ( 7 ). Treatment strategies across cancers are moving towards personalised medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor immune cell infiltration, inhibition of glycolysis pathway, regulation of ferroptosis, and regulation of the ceRNA network are an intense focus of research of tumor gene therapies, which are extensively applied in the research and treatment of ESCA ( Baba et al, 2020 ; Liu et al, 2021b ; Feng et al, 2021 ; Lonie et al, 2021 ; Shi et al, 2021 ; Shishido et al, 2021 ). Nevertheless, there area few studies on the thorough study of YTHDF1 in ESCA, especially the relationship between YTHDF1 and ESCA immune cell infiltration, glycolysis, ferroptosis, and the ceRNA network.…”
Section: Introductionmentioning
confidence: 99%
“…Although radical resection, radiotherapy, and chemotherapy for ESCA have made significant progress, the 5-year survival rate of ESCA patients is still very low ( Kelly, 2019 ; Yang et al, 2020a ; Thrift, 2021 ). The occurrence, development, and recurrence of ESCA involve a variety of important signal transduction pathways and biological functions in the human body ( Yang et al, 2020b ; Liu et al, 2021a ; Lonie et al, 2021 ; Thrift, 2021 ). Therefore, finding biomarkers involving multiple biological functions and exploring the pathogenesis of ESCA can provide a better reference for tumor diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In EC, the tumor–immune microenvironment is largely immunosuppressive and pro-tumorigenic, characterised by an exhausted adaptive immune response in addition to a predominant infiltration by neutrophil-like, myeloid-derived suppressor cells (MDSC). 2 Research into the effects of chemotherapy and/or radiation on the tumor–immune microenvironment have largely concluded that these treatments have immunostimulatory and abscopal effects, which lead to an immunogenic tumor cell death response mediated by T-cell priming and antigen presentation. 3 However, emerging evidence suggests that subjecting solid tumors with a preexisting, immunosuppressive microenvironment to neoadjuvant treatment may, in fact, further enhance immunosuppression through a number of mechanisms involving the chronic inflammatory response and its mediators enhancing the effects of MDSCs and the polarization of other immune cells to a pro-tumorigenic state.…”
mentioning
confidence: 99%